DUAL ACCOUNTABILITY : MANIFESTASI AKUNTABILITAS DOMPET DHUAFA SULAWESI SELATAN (AKUNTIA JURNAL Jurnal Akuntansi, Terpercaya, Menginspirasi dan Asli, 2019)
Accountability is no longer understood as accountability to the stockholder with the financial statements as the only form of accountability. This research aimed to exploration the understanding and meaning of amil Dompet Dhuafa of South Sulawesi (DD Sulsel) on the values of Zakat, Infak and Sedekah (ZIS), and influence of the meaning to create accountability in DD Sulsel. This research used the spiritual paradigm, with islamic spiritual ethnometodology as the research method. The research results indicated that the values understood and embraced by amil DD Sulsel were the obedience, fairness, caring, and welfare, as the meaning of ZIS values. The four mentioned values were internalized and crystallized into the islamic holy spirit which could inspire amil to become trusty, professional, and accountable in implementing accountabilitty in the management of ZIS in DD Sulsel. The accountability in the management of ZIS in DD Sulsel was a dual accountability, i.e the islamic spiritual accountability and the social accountability. In practice, the dual acoountability is implemented by the spirit of ihsan.